2012
DOI: 10.1007/s00267-012-9947-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Selenium by the Bryophyte Hygrohypnum ochraceum in the Fountain Creek Watershed, Colorado

Abstract: Aquatic bryophytes, Hygrohypnum ochraceum, were deployed "in situ" at 14 sites in the Fountain Creek Watershed, spring and fall, 2007 to study selenium (Se) accumulation. Dissolved, total, and pore (sediment derived) water samples were collected and water quality parameters determined while plants were exposed to the water for 10 days. There was a trend showing plant tissue-Se uptake with distance downstream and we found a strong correlation between Se in the water with total hardness in both seasons. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Similarly, Turner ( 2009 ) found dissolved Se in water from site LF-4 (Lower Fountain Creek, Pueblo, CO, Table 1 ) averaging 9.7 µg/l in spring and 18.6 µg/l in the fall. As part of an extensive monitoring study Herrmann et al ( 2012 ) found bioconcentration factors in the aquatic plant, H. ochraceum , exposed for 10 days in-stream, as high as 5.8 × 10 3 at Green Mountain Falls site (UF-1) and 1.5 × 10 4 at the Manitou Springs site (UF-2) in the fall of 2007. The main conclusion by Herrmann et al ( 2012 ) was that the aquatic plants ( H. ochraceum ) used in the study were suitable indicators of Se-bioavailabilty and that Se potentially would enter additional trophic levels, including fish, in Fountain Creek.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, Turner ( 2009 ) found dissolved Se in water from site LF-4 (Lower Fountain Creek, Pueblo, CO, Table 1 ) averaging 9.7 µg/l in spring and 18.6 µg/l in the fall. As part of an extensive monitoring study Herrmann et al ( 2012 ) found bioconcentration factors in the aquatic plant, H. ochraceum , exposed for 10 days in-stream, as high as 5.8 × 10 3 at Green Mountain Falls site (UF-1) and 1.5 × 10 4 at the Manitou Springs site (UF-2) in the fall of 2007. The main conclusion by Herrmann et al ( 2012 ) was that the aquatic plants ( H. ochraceum ) used in the study were suitable indicators of Se-bioavailabilty and that Se potentially would enter additional trophic levels, including fish, in Fountain Creek.…”
Section: Resultsmentioning
confidence: 99%
“…Among other issues were flash floods leading to erosion, resulting in questions about the sources of Se, the movement and varying concentrations of Se in the watershed, and was there uptake of the metalloid into the stream biota including fish? Because of an earlier study by Nimmo et al ( 2006 ) who showed the cadmium and zinc accumulation by an aquatic plant species, Hygrohypnum ochraceum, in the upper Arkansas River, Colorado, we used H. ochraceum as an indicator organism to determine Se-uptake in the Fountain Creek watershed (Herrmann et al 2012 ). Four findings of this effort were that the: (1) plants obtained more Se in the basin with travel-distance downstream, (2) plants showed a trend to take up more Se with total hardness in the spring versus the fall, (3) bryophytes accumulated Se thousands of times above the Se-concentration in ambient water, particularly noticeable in the upper reaches of the watershed in the fall, and most important, (4) the bryophytes appeared to be a suitable indicator of Se bioavailability to other trophic levels.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations